(3LejdI (B( (3NUjdI (B) (3CQHGH GdehGUO aj TQM YbdjI GJQGH GdbUGFOs - (3HQgGf GdOjf CHh eMeO EHQGgje Hf YeQ Hf EHQGgje GdLYHQis; (3bGSe Hf ajQg GdTGWHj, CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GdgefG hVY GdcdGe OdjdkG Ydi eYGfi GdNWGH hHYO adeG jSQ Gddg JYGdi EceGd cJGH cfR GdeYGfi ai TQM NQQ GdCeGfi LejdI CQHGH GdeQGUO LGeYI ThGQO GdebfY ai CSdhH eHOY s
(3BNQgG (B:s
(3gPG GdefgGL YdeG Ydi cjajI GdESJNQGL abQH GdHYjO hLeY GdTQjO aGYJeO Ydjg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3QhGjI GdTjN Sja GdOjf Hf GdLfOi Gdebhi GdMfais
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3bQGCJ hJLhjO (B28) s
Keywords: (3GdbQGAGJ hGdJLhjOs